2005
DOI: 10.1073/pnas.0504029102
|View full text |Cite
|
Sign up to set email alerts
|

A database analysis method identifies an endogenous trans-acting short-interfering RNA that targets the Arabidopsis ARF2, ARF3 , and ARF4 genes

Abstract: Two classes of small RNAs, microRNAs and short-interfering RNA (siRNAs), have been extensively studied in plants and animals. In Arabidopsis, the capacity to uncover previously uncharacterized small RNAs by means of conventional strategies seems to be reaching its limits. To discover new plant small RNAs, we developed a protocol to mine an Arabidopsis nonannotated, noncoding EST database. Using this approach, we identified an endogenous small RNA, trans-acting short-interfering RNA-auxin response factor (tasiR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
249
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 275 publications
(255 citation statements)
references
References 50 publications
5
249
1
Order By: Relevance
“…Similar results for these genes were obtained by Vazquez et al (2004). Subsequent studies by us (Yoshikawa et al 2005) and other workers Williams et al 2005) revealed that most of the other up-regulated genes identified in this microarray analysis are also targets of siRNAs from unrelated transcripts and showed that the elevated expression of these genes in zip, rdr6, and sgs3 is correlated with the absence of these "trans-acting" siRNAs.…”
Section: Identification Of Ta-sirnassupporting
confidence: 72%
See 2 more Smart Citations
“…Similar results for these genes were obtained by Vazquez et al (2004). Subsequent studies by us (Yoshikawa et al 2005) and other workers Williams et al 2005) revealed that most of the other up-regulated genes identified in this microarray analysis are also targets of siRNAs from unrelated transcripts and showed that the elevated expression of these genes in zip, rdr6, and sgs3 is correlated with the absence of these "trans-acting" siRNAs.…”
Section: Identification Of Ta-sirnassupporting
confidence: 72%
“…TAS1 and TAS2 do not appear to be conserved outside Arabidopsis thaliana. TAS3 regulates three members of the ARF family of auxin-related transcription factors (ARF2, ETT/ARF3, and ARF4) and is conserved throughout higher plants Williams et al 2005). …”
Section: Identification Of Ta-sirnasmentioning
confidence: 99%
See 1 more Smart Citation
“…The target is specified by the perfect or near-perfect sequence complementarity between the miRNA and its respective binding site on the targeted mRNA (Aukerman and Sakai, 2003;Wang et al, 2005a;Williams et al, 2005b). Experimental evidence indicates that there is usually a single miRNA binding site anywhere along the target mRNA.…”
Section: Targets Of Micro Rnamentioning
confidence: 99%
“…Leaf development is regulated by modulating the expression of class-III homeodomain leucine zipper (HD-ZIP) transcription factor genes, which control leaf patterning along adaxial/abaxial axis (Juarez et al, 2004). PHABULOSA (PHB), PHAVOLUTA (PHV), and REVOLUTA (REV) are three closely related Arabidopsis HD-ZIP transcription factors that are the targets of miR165 and miR166 (Emery et al, 2003;Bao et al, 2004;Bowman, 2004;Juarez et al, 2004;Mallory et al, 2004b;Zhong and Ye, 2004;Kim et al, 2005;Williams et al, 2005b;Ko et al, 2006). Altered expression of miR165 and miR166 resulted in leaf developmental abnormalities in Arabidopsis and corn (Juarez et al, 2004).…”
Section: Functions Of Micro Rnamentioning
confidence: 99%